2013
DOI: 10.3109/09546634.2012.739278
|View full text |Cite
|
Sign up to set email alerts
|

Body image altered by psoriasis. A study based on individual interviews and a model for body image

Abstract: An altered body image has a psychosocial impact on patients with visible psoriasis that may result in increased body coverage, sexual inhibitions and reduced exercise activity. This further affects self-image negatively and influences how people with psoriasis handle the risk of metabolic syndrome. Assessment of patient body image using components of the BIM increases the possibility of identifying important psychosocial aspects of psoriasis and the related risk of metabolic syndrome and is thus a valuable sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 17 publications
7
50
0
1
Order By: Relevance
“…Prominent physical symptoms are itching, pain, flaking/scaling and red patches of skin, any of which can significantly impact patients' emotional states and social functioning. Previous research has revealed that psoriasis has altered patients' body image negatively that resulted in psychosocial impairment of patients with visible symptoms [27], while the present study also found that visible physical symptoms might affect various aspects of patients' daily life. Patients might experience difficulties in maintaining former social interactions or establish new interpersonal relationships.…”
Section: Discussionsupporting
confidence: 48%
“…Prominent physical symptoms are itching, pain, flaking/scaling and red patches of skin, any of which can significantly impact patients' emotional states and social functioning. Previous research has revealed that psoriasis has altered patients' body image negatively that resulted in psychosocial impairment of patients with visible symptoms [27], while the present study also found that visible physical symptoms might affect various aspects of patients' daily life. Patients might experience difficulties in maintaining former social interactions or establish new interpersonal relationships.…”
Section: Discussionsupporting
confidence: 48%
“…[17][18][19][20] Our findings throw light on ways in which people with CTCL adapt to and cope with their illness. This supports research in other dermatological conditions and cancer which has documented the sometimes devastating burden of disfiguring diseases.…”
Section: Discussionmentioning
confidence: 76%
“…Psoriasis in children is characterized by well‐defined erythematous papules and plaques of varying size with silvery scales, most commonly in visible areas such as the scalp and face, and on the elbows and knees . While research in adult populations confirms that appearance‐related issues are important for understanding HRQoL in psoriasis in general, such difficulties may be particularly salient in adolescents, where peer pressure and the desire to ‘fit in’ often play a significant role in their everyday life and psychosocial development …”
mentioning
confidence: 99%